Supporting gifted and talented pupils in the secondary school - Thomson, Moira; Sage eBooks (London : Paul Chapman, 2006)
Taking a whole school approach to educating gifted and talented pupils in mixed-ability schools, this book is packed with practical ideas for lessons and contains plenty of case studies.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Gifted children -- Education (Secondary) -- Great Britain; Electronic books